Efektivitas Metode Pembelajaran Student Centered Learning Menggunakan Aplikasi Powtoon untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PPKn di SMPN 1 Sindangagung (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to increase student motivation in learning Pancasila and Civics Education through the application of student-centered learning methods assisted by the Powtoon application. The research used a quantitative approach with a pre-experimental design of the One Group Pretest-Posttest Design type. The research population was all 153 students in grade VIII at SMP Negeri 1 Sindangagung, while the research sample was class VIII A with 28 students. Data were collected through observation, questionnaires, and documentation, then analyzed using quantitative descriptive statistics. The results showed that the average pretest questionnaire score was 32.79, while the posttest score increased to 44.18, with an increase of 11.39. The t-test produced a t-count value of 20.362, which was greater than the t-table value of 2.056. Thus, Ha was accepted, which meant that the student-centered learning method assisted by Powtoon was effective in increasing student learning motivation in Pancasila and Civics Education at SMP Negeri 1 Sindangagung.